Traditionally used ethnomedicinal plants for the treatment of cancer and diabetes in Nepal - Paudel, Mukti Ram; Sharma, Sujata; Poudeyal, Mukti Ram (Botanica Orientalis: Journal of Plant Science, 2025)
Traditional medicines play an important role in healthcare provision. The traditional system of medicine based on medicinal plants in Nepal presents a strong relationship among natural remedies, health, diet, and folk healing practices. In recent years, evidence supports the effectiveness of herbal medicines in controlling blood sugar levels, functioning as anti-tumorous agents, and holistically boosting the immune system. Limited baseline research and current knowledge gaps, however, make it difficult to establish evidence for traditional knowledge of plant-based medicines that treat cancer and diabetes. This study aimed to identify and document the medicinal plants used by traditional medicine practitioners in Nepal to treat cancer and diabetes and to explore the intricate socio-cultural relationship. More than 70 published papers were retrieved from the online bibliographical database. The scientific name, common name, family, parts used, and their role in the treatment of diabetes and cancer were enumerated. The present review reported that 125 species belonging to 72 families have been used in Nepal. This review contributes to the knowledge of certain medicinal plants that are prevalent for the prevention and treatment of cancer (tumor) and diabetes, and which can be further investigated to produce new drugs with fewer side effects and better patient compliance.